Oral Health of Children with Severe Neurological Impairment in Ireland - Crowley, Robyn (Trinity College Dublin. School of Dental Sciences. Discipline of Dental Science, 2025)
This thesis comprises two different studies with a shared focus on the oral health of children with severe neurological impairment (SNI). SNI is defined as "a group of disorders of the central nervous system which arise in childhood, resulting in motor impairment, cognitive impairment and medical complexity, and where much assistance is required in the activities of daily living. The impairment is permanent but can be progressive or static" (J. Allen et al. 2020). Study One is a cross-sectional study investigating the oral health of children with SNI through a questionnaire and an oral health assessment. Forty-two children and their parents were recruited from Children's Health Ireland (CHI) to take part. All forty-two parents completed the oral health questionnaire and 38 children attended for an oral health assessment appointment. The most common underlying diagnosis was CP. The majority attended a dentist in a hospital setting (60%), rather than in the community. The majority of participants' teeth were brushed with some form of resistance (n=34, 81%) and the most commonly reported perceived barrier to oral health care was "dental centres/units that treat special needs patients are rare and limited". Mean D3vcMFT+d3vcmft was 0.46 (SD=1.6) and mean OHI-S was 1.45 (SD=1.3). There was no difference in D3vcMFT+d3vcmft or OHI-S in those with CP versus genetic diagnoses or in those fed orally and those fed enterally. C-I was statistically significantly higher in those with enteral feeding compared to those fed orally. A preventive treatment need was noted in 100% participants and 11% required dental care under general anaesthesia. These findings highlight the oral health challenges faced by children with SNI and their families, including limited access to care, limited support for families and reliance on hospital-based services. This study emphasised the need for early referral and better education for both healthcare provider and parents. Study Two aimed to create and assess acceptability of a short educational video demonstrating toothbrushing for parents of children with SNI. Its acceptability was assessed through the Generic Form of the Theoretical Framework of Acceptability (Sekhon, Cartwright, and Francis 2017, 2022). This was completed by 23 HCWs and 20 parents and carers. The video received overwhelmingly positive feedback from both groups with suggestions to use it in waiting rooms in clinics. The results indicate the video is a valuable educational tool, with potential for future refinement based on ongoing feedback.
APPROVED
Keywords: severe neurological impairment; paediatric oral health; special care dentistry; children with medical complexity